AP physics C prep (Penguin Random House, 2023)
EVERYTHING YOU NEED TO HELP SCORE A PERFECT 5! Ace the AP Physics C Exam with this comprehensive study guide--including 3 full-length practice tests with complete answer explanations, thorough content reviews, targeted exam strategies, and bonus online extras.--Publisher's website.